1989
DOI: 10.1557/proc-162-347
|View full text |Cite
|
Sign up to set email alerts
|

Metallization of Semiconducting Diamond: Mo, Mo/Au and Mo/Ni/Au

Abstract: PblIc reporting burden 1Wr this collection of bIfornalelon is 401maled to avrage I hourf Per ANSPOM. APRI 2 1993 9 -07481 l')'J Approved for public release; distribution is unlimited. ABSTRACT (Awmun 200 waro)A processing technology has been developed to make ohmic contacts to naturally doped semiconducting diamond. The approach follows, as far as possible, conventional photolithographic techniques for metallization of semiconductors currently in use in the microelectronic industry.Ohmic contacts have been suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…A further striking feature of the data is the degree of coincidence between the crosslink positions and P-site footprints, a phenomenon which has also been noted in the 23S RNA, with regard to cross-links from the aminoacyl moiety of tRNA (Steiner et al, 1988;Mitchell et al, 1993) and footprints from its 3'-terminus (Moazed and Noller, 1989). In addition to those cases just discussed, the P site cross-link at nucleotide 966 in helix 31 and the P and E site cross-links at nucleotide 693 in helix 23 ( Figure 5) are identical with P site footprint positions (Moazed and Noller, 1990); from the cross-link data, it can be concluded that the loop-ends of these two helices (23 and 31) are indeed directly involved in the decoding region. From similar cross-linking studies with mRNA, helices 18 and 34 (Dontsova et al, 1992) and now helix 22 (J.Rinke-Appel et al, in preparation) are also part of the same neighbourhood.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…A further striking feature of the data is the degree of coincidence between the crosslink positions and P-site footprints, a phenomenon which has also been noted in the 23S RNA, with regard to cross-links from the aminoacyl moiety of tRNA (Steiner et al, 1988;Mitchell et al, 1993) and footprints from its 3'-terminus (Moazed and Noller, 1989). In addition to those cases just discussed, the P site cross-link at nucleotide 966 in helix 31 and the P and E site cross-links at nucleotide 693 in helix 23 ( Figure 5) are identical with P site footprint positions (Moazed and Noller, 1990); from the cross-link data, it can be concluded that the loop-ends of these two helices (23 and 31) are indeed directly involved in the decoding region. From similar cross-linking studies with mRNA, helices 18 and 34 (Dontsova et al, 1992) and now helix 22 (J.Rinke-Appel et al, in preparation) are also part of the same neighbourhood.…”
Section: Discussionsupporting
confidence: 62%
“…'P-34' indicates the site of cross-linldng to position 34 of P site bound tRNA (Prince et al, 1982). Solid triangles and circles denote sites of footprinting from A or P site bound tRNA, respectively (Moazed and Noller, 1990). Sites of cross-linking to ribosomal proteins S7, Sll, S13 and S19 are also included.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations